Gambaran Perilaku Picky Eater dan Faktor yang Melatar Belakanginya pada Anak Usia 2-4 Tahun di RW XII Kelompok Bermain dan Raudhatul Athfal Alamterpadu Uwais Al Qorni Surakarta - Ika Budi Wijayanti; Hutari Puji Astuti; Danik Riawati (Jurnal Gizi Prima (Prime Nutrition Journal), 2020)
Background: Researcher knows the phenomenon experienced by children picky eater .This is proven results early screening conducted by researcher , revealed the children had as many as 82 % picky eater , but behavior picky eater experienced by children classified as slight extent because not until affect growth .As many as 45 % mother feel it as a problem Research Methods : Still a little research on picky eater done in Indonesia , but is still very picky eater of information about needs to develop .In general the knowledge to know the reason that mother about picky eater such behavior in children age a preschool program in kindergarden Uwais Qorni Surakarta. Research Result : The result is a low variation in the types of food that children consume daily. In general, children eat the same type of food a day and the type of food does not differ much every day. The low variety of child food types is caused by the mother cooking only once for one day, on the grounds that the mother does not have enough time. In fact, the majority of informants in this study were housewives who spent a lot of time at home. Conclusion : The behavior of the picky eater is a common dietary phase for children. The common picky eater behaviour found in this research is limited food variation, so that the child looks to choose the type of food they are being smoked.